2009
DOI: 10.1093/ndt/gfp259
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary predialysis education decreases the incidence of dialysis and reduces mortality--a controlled cohort study based on the NKF/DOQI guidelines

Abstract: MPE based on the NKF/DOQI guidelines may decrease the incidence of dialysis and reduce mortality in late-stage CKD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
132
1
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(146 citation statements)
references
References 26 publications
3
132
1
10
Order By: Relevance
“…28 In Taiwan, the rate of misdiagnosing CKD may have been modest since 2004, because a CKD prevention program has made nearly all patients with CKD diagnosis receive specialist consultation. [29][30][31] In light of this information, our validation shows fair reliability for CKD identification in this study. Identifying AKI by the dialysis procedure also introduced limitations.…”
Section: Study Strengths and Limitationssupporting
confidence: 61%
See 1 more Smart Citation
“…28 In Taiwan, the rate of misdiagnosing CKD may have been modest since 2004, because a CKD prevention program has made nearly all patients with CKD diagnosis receive specialist consultation. [29][30][31] In light of this information, our validation shows fair reliability for CKD identification in this study. Identifying AKI by the dialysis procedure also introduced limitations.…”
Section: Study Strengths and Limitationssupporting
confidence: 61%
“…Reliability of ICD-9-CM codes for AKI and CKD was validated. [29][30][31] Investigation of AKI recovery effect was conducted across broad varieties of patient groups. Effects from timevarying covariates were inspected.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…In addition to a study, which showed an improvement in the outcome of CKD patients, 4 a controlled cohort study 5 showed that the change in renal function of patients with CKD stages 3-5 was 0.008 AE 0.139 mL/ min per 1.73 m 2 per month while receiving the MDC during 12 months of the follow-up. Often the CKD patients were referred at an advanced stage of renal failure, only few months before or even a few weeks prior to ESRD.…”
Section: Introductionmentioning
confidence: 99%
“…La educación multidisciplinar prediálisis basado en las directrices NFK/DOQI puede disminuir la incidencias de diálisis y reducir la mortalidad en los pacientes con ERC en la etapa tardía (34) , y puede suponer un retraso en la progresión de la enfermedad renal (35) . A pesar de los beneficios demostrados que aporta esta intervención, en nuestro estudio, un porcentaje de pacientes inferior al 40% fueron atendidos en la consulta de enfermería en la etapa previa al inicio de la TSR.…”
Section: Discussionunclassified